The Role of Cognitions and Beliefs in Trichotillomania: A Qualitative Study Using Interpretative Phenomenological Analysis. Issue 4 (12th August 2015) - Rehm, Imogen C.; Nedeljkovic, Maja; Thomas, Anna; Moulding, Richard
Abstract : Trichotillomania (TTM) is characterised by the removal of one's hair, causing hair loss. Phenomenological research on TTM has investigated its associated behavioural and affective factors. Few studies have investigated the possible role of cognitions and beliefs, despite emerging support for cognitive therapies in treating this disorder. This study aimed to explore and describe the cognitions and beliefs that contribute to the onset and maintenance of hairpulling in TTM. Eight women with TTM participated in semi-structured, in-depth interviews to explore their experience of cognitions and beliefs before, during and after typical hairpulling episodes. Interviews were analysed using the qualitative method of Interpretative Phenomenological Analysis. Six superordinate themes of beliefs were identified as important: negative self-beliefs, control beliefs, beliefs about coping, beliefs about negative emotions, permission-giving beliefs, and perfectionism. These preliminary findings suggest that cognitions may play an important role in TTM phenomenology. Future quantitative research on the role of cognitions and beliefs in TTM in larger samples has the potential to advance cognitive-behavioural models and treatments of this poorly understood disorder.